In-situ quantification of minor compounds in pressurized carbon dioxide using Raman Spectroscopy - Rodriguez-Meizoso, Irene; Quiño, Jaypee; Bräuer, Andreas (Journal of Supercritical Fluids, 2013)

One-dimensional Raman spectroscopy and shadowgraphy for the analysis of the evaporation behavior of acetone/water drops - Quiño, Jaypee; Hellwig, Thomas; Griesing, Matthias; Pauer, Werner; Moritz, Hans-Ulrich; Will, Stefan; Bräuer, Andreas (International Journal of Heat and Mass Transfer, 2015)
Temporally and spatially resolved composition profiles were measured along a line through the drops using one-dimensional Raman spectroscopy. Shadowgraphs of the evaporating drops were acquired, from which the drop shrinkage was derived. Due to the good spatial (120 mu m) and temporal (1 s) resolution of the one-dimensional Raman experiment the evolution of the radial composition profiles through the drop could be followed showing that the diffusion-process inside the drop plays an important role in the binary evaporation process. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Acoustic levitation; Water/acetone mixture; Surface regression rate; 1D-Raman line imaging; Mass transport; Drop; Evaporation

Quantification of the mass transport in a two phase binary system at elevated pressures applying Raman spectroscopy: pendant liquid solvent drop in a supercritical carbon dioxide environment - Bräuer, Andreas; Knauer, Oliver; Quiño, Jaypee; Leipertz, Alfred (International Journal of Heat and Mass Transfer, 2013)

Supercritical drying of aerogel: In situ analysis of concentration profiles inside the gel and derivation of the effective binary diffusion coefficient using Raman spectroscopy - Klima, Tobias; Quiño, Jaypee; Quiño, Jaypee; Rühl, Martin; Klima, Tobias; Ruiz, Francisco; Will, Stefan; Bräuer, Andreas (Journal of Supercritical Fluids, 2016)
We here experimentally visualize in situ temporally and spatially resolved composition and concentration fields developing inside silica aerogels during the supercritical drying process. For the extraction of the pore liquid ethanol we used supercritical carbon dioxide. The evolution of the composition profiles inside the gel was measured via one-dimensional Raman spectroscopy. The composition profiles were converted into concentration profiles using an equation of state. The evolution of the concentration fields shows that ethanol is continuously transported out of the gel. On the contrary CO2 is first transported into and at later drying times (before the depressurization) out of the gel structure. The binary diffusion coefficient was derived as a function of the composition and found to vary by two orders of magnitude for different stages of the drying process. (C) 2015 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: Aerogel; Supercritical drying; Diffusion coefficient; 1D Raman spectroscopy; In situ measurements; Mass transport; Pore diffusion